Predicting breakfast consumption: A comparison of the theory of planned behaviour and the health action process approach - Mullan, Barbara; Wong, C.; Kothe, E.; Maccann, C. (Emerald Group Publishing Limited, 2013)
Purpose: Breakfast consumption is associated with a range of beneficial health outcomes including improved overall diet quality, lower BMI, decreased risk of chronic disease, and improved cognitive function. Although there are many models of health and social behaviour, there is a paucity of research utilising these in breakfast consumption and very few studies that directly compare these models. This study aims to compare the theory of planned behaviour (TPB) and the health action process approach (HAPA) in predicting breakfast consumption. Design/methodology/approach: University students (N=102; M=19.5 years) completed a questionnaire measuring demographics, TPB and HAPA motivational variables, and intentions. Behaviour and HAPA volitional variables were measured four weeks later. Findings: Using structural equation modelling, it was found that the TPB model was a superior fit to the data across a range of model indices compared to the HAPA. Both models significantly predicted both intentions and behaviour at follow up; however, the TPB predicted a higher proportion of the variance in breakfast consumption (47.6 per cent) than the HAPA (44.8 per cent). Further, the volitional variables did not mediate the intention-behaviour gap, and the data were not an adequate statistical fit to the model compared to the TPB.Research limitations/implications: The results support the use of the TPB and show that some aspects of the HAPA are useful in predicting breakfast consumption, suggesting that risk perception and self-efficacy be targeted in interventions to increase behaviour. The volitional variables did not appear to mediate breakfast consumption indicating that intention is still the strongest predictor, at least in this behaviour. Originality/value: The current study is the first to compare the TPB and HAPA in predicting breakfast consumption.